1988
DOI: 10.1159/000124934
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Investigation of the Magnocellular Peptidergic Hypothalamo-Neurohypophysial System of the Rat Chronically Stimulated by Long-Term Administration of Hypertonic Saline

Abstract: The hypothalamic supraoptic (SON) and paraventricular nuclei (PVN), median eminences (ME) and neural lobes (NL) of normally hydrated control rats (group 1), and of rats drinking 2% NaCl for 7 (group 2), 30 (group 3) or 90 days (group 4) were investigated using immunohistochemistry for neurophysins (NP), arginine vasopressin (AVP) or oxytocin (OXY). Animals from the 3 experimental groups showed equivalent decreased levels of immunoreactive NP in the SON and PVN, but the greatest decrease was in the SON. Dendrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…These studies, however, employed uninephrectomized rats offered salt drinking only. In our opinion, they are not suitable models to study the role of mineralocorticoids on AVP mRNA expression because salt drinking alone as well as dehydration due to hypertonicity markedly increase AVP and OT mRNA levels and affect the immunoreactive AVP peptide content in the absence of administered mineralocorticoid [24, 36]. In agreement with these authors, we also found increased mRNA for AVP in the PVN from rats drinking 3% NaCl only but not receiving DOCA.…”
Section: Discussionsupporting
confidence: 88%
“…These studies, however, employed uninephrectomized rats offered salt drinking only. In our opinion, they are not suitable models to study the role of mineralocorticoids on AVP mRNA expression because salt drinking alone as well as dehydration due to hypertonicity markedly increase AVP and OT mRNA levels and affect the immunoreactive AVP peptide content in the absence of administered mineralocorticoid [24, 36]. In agreement with these authors, we also found increased mRNA for AVP in the PVN from rats drinking 3% NaCl only but not receiving DOCA.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have reported activation of magnocellular OT neurons and parvocellular CRH neurons in the PVN under hyperosmotic conditions (Lightman & Young, 1987; Van Tol et al. , 1987; Dellmann et al. , 1988; Carter & Murphy, 1989; Amaya et al.…”
Section: Discussionmentioning
confidence: 98%
“…Here, we also report a decrease in 10% w/v sucrose intake in ad libitum fed and watered rats treated centrally with AM. OT has been described as a general satiety factor , Lokrantz et al 1997, Blevins et al 2004 and has also been shown to inhibit food , Sclafani et al 2007, water (Verty et al 2004), salt (Dellmann et al 1988, Blackburn et al 1992a,b, 1993, Murphy & Samson 1995, Allen et al 1997, and sucrose intakes among others (Lokrantz et al 1997, Sclafani et al 2007. If central AM is, indeed, activating OT neurons as we hypothesize, then the effects of AM should not be specific but rather AM would be a satiation cue for all ingestive behaviors.…”
Section: Discussionmentioning
confidence: 67%
“…Salt loading an animal will lead to significant increases in tissue Ot mRNA levels and plasma OT concentrations (Balment et al 1980, Van Tol et al 1987, Dellmann et al 1988, Verbalis & Dohinics 1991, Ozaki et al 2004. The effects of altered central AM levels on hypertonic saline-stimulated plasma OT levels were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation